Analysis of Promotion Effectiveness Using Instagram Social Media at Zaky & Dicky Cafe - Librina Tria Putri; Royansyah Putra; Adi Setiawan (Khazanah Sosial, 2022)
The purpose of this study was to determine whether Zaky & Dicky Cafe's Instagram advertising efforts were effective. Instagram is an image and video sharing program that allows users to take photos, record videos, apply digital filters, and share their creations on various social networking networks. To determine its efficacy on social interaction, researchers used the EPIC analysis model (empathy, persuasion, impact, and communication) and tested it individually using the average score technique. The population and samples were taken from customers of Zaky & Dicky Cafe. Sampling was carried out using a census technique of 300 samples. Results Based on the research, Zaky & Dicky Cafe's marketing with Instagram social media is effective. The Persuation dimension is the highest dimension of the four EPIC Models. Consumers are satisfied with the reality they receive based on the promotion of Zaky & Dicky Cafe using Instagram social media.